Pengembangan Usaha Sablon Kaos Kustom Nyala Tshirt Berbasis Digital dan Ramah Lingkungan untuk menumbuhkan Jiwa Kewirausahaan Mahasiswa - Yuliati, Yuliati; Indriyatni, Lies; Mutiarasari, Anggun; Isnain, Ariyantiano Bagus Muchamad; Jannah, Diah Riyadlil; Saudah, Nurus (Fokus ABDIMAS, 2024)
The clothing industry, particularly t-shirts, has experienced rapid growth as a means of self-expression and lifestyle in recent decades. The demand for custom t-shirts has increased alongside society's interest in unique and personalized clothing. Digital technology and printing have facilitated the rapid and high-quality production of custom t-shirts. Custom t-shirt printing businesses offer promising business opportunities by understanding market trends, consumer needs, and utilizing the latest technology. "Nyala T-Shirt" not only offers custom t-shirts with unique designs but also is committed to reducing plastic waste through the use of eco-friendly packaging. Through strategic marketing, including promotion through social media, collaboration with influencers, and direct sales, this business aims to increase brand awareness and sales of custom t-shirts. The goal is not only to generate profits but also to inspire students to develop their entrepreneurial spirit and hone their entrepreneurial skills. With creativity, product quality, and the right use of technology, this custom t-shirt printing business is expected to grow sustainably and serve as a platform for innovation and creativity. Keywords: T-shirt printing, entrepreneurial skill